Review Optimalisasi Penggunaan Produk Industri Strategis Nasional untuk Mendukung Kesiapan Alutsista TNI AL (Universitas Trunojoyo Madura, 2022)
The implementation of the main tasks of the Indonesian Navy must be supported by the strength of the defense doctrine, human resources, and the main tools of the Indonesian Navy's reliable weapon system (alutsista). Observing the current condition of the Indonesian Navy, it is still far from the conditions that are expected to be able to carry out its main tasks, especially with the state of readiness of the defense equipment system. The current condition of the TNI AL's strength when compared to the strength of neighboring countries in the ASEAN region is still lagging behind. To be able to improve the readiness of the Indonesian Navy's defense equipment, including optimizing the use of national strategic industrial products to support the readiness of the Indonesian Navy's defense equipment, which has a fairly reliable ability to produce, assist maintenance and repair of defense equipment. The purpose of this paper is to find out and analyze the implementation of the use of national strategic industrial products, the implications for the support of the Indonesian Navy's defense equipment and how the solutions are to support the readiness of the Indonesian Navy's defense equipment in order to increase national security. This writing uses a normative juridical approach through assessing the capabilities of national strategic industries, fulfilling the needs of the Navy's defense equipment, human resources capabilities in technology transfer, budget support and optimizing the use of national strategic industrial products to increase national resilience. The conclusion is that the use of national strategic industrial products has a close relationship in terms of supporting the readiness of the Navy's defense equipment and increasing national security.